Perception of Social Health Insurance Program among Community People in Pokhara, Nepal - Sharma, Sharada; Banjara, Sobita (Janapriya Journal of Interdisciplinary Studies, 2020)
Perception of social health insurance program is the way in which it is understood or interpreted in terms of different factors; quality of care service delivery adequacy, benefits of program, convenience, price, providers attitude, peer pressure, Community beliefs and attitudes. The main aim of this study is to identify community people’s perception and the factors influencing the perception of people towards social health insurance program. Data from total of 105household registered in insurance program (insured) were collected. Descriptive cross sectional study design was used. The data were analyzed and interpreted by using descriptive and inferential statistics through the computer program SPSS 16 version and presented in tables. Findings revealed that age group range from 20 to 77 years, 72.4 percent family size 5 or below 74.3 percent utilized the insurance services from the accredited health facility. Regarding the reason for enrollment, 83.8 percent said financial protection against illness, 50.8 percent gave the reason that they had to buy drugs outside facility as the main reason for not renewing the program in future. Price of program related response was top perceived factor with mean 3.97±0.70 whereas provider attitude was low perceived factor with mean 1.95± 0.58. The study concluded that the price of program related factors were the top perceived factors whereas provider attitude related factors were low perceived factors that may influence for the perception of community people towards social health insurance program.